2009
DOI: 10.1590/s1677-04202009000200005
|View full text |Cite
|
Sign up to set email alerts
|

I. Heat stress in Triticum: kinetics of Ca and Mg accumulation

Abstract: In heat stressed genotypes of Triticum aestivum L. (Sever and Golia) and Triticum turgidum subsp. durum (Acalou and TE 9306), chosen according to its genetic background diversity, Ca and Mg accumulations were correlated with its photosynthetic performance. It was found that with high temperatures the concentrations of Ca increased in the shoots, whereas the accumulation of Mg augmented only in bread wheat genotypes. Under heat stress, the pattern of electrolytes release in Golia and Acalou remained similar, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…This may be attributed to the influence of heat stress induced by late sowing on Ca 2+ mobilisation during grain filling. In this respect, [ 113 ] reported that Ca 2+ assimilation to the shoots and spikes increased in heat-stressed wheat, alleviating heat injury [ 114 ] and limiting oxidative damage [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the influence of heat stress induced by late sowing on Ca 2+ mobilisation during grain filling. In this respect, [ 113 ] reported that Ca 2+ assimilation to the shoots and spikes increased in heat-stressed wheat, alleviating heat injury [ 114 ] and limiting oxidative damage [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, changing the sowing date influenced the mineral contents of wheat straw ( Table 10 ). The level of Ca 2+ content significantly increased in late-sown wheat straw as a mechanism of heat tolerance in wheat, which is associated with the maintenance of net carbon assimilation rates [ 113 ]. On the other hand, the K + level increased in late-sown wheat straw ( Table 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Mg 2+ strongly interacts with nucleophilic ligands (i.e., phosphoryl groups) through ionic bonding (Günther, 1981), but under heat stress, although might stabilize the covalent bonds of chlorophylls, its depression might limit the synthesis of this molecule (Marschner, 1995). Nevertheless, it has been reported (Dias et al, 2009d) that, in the particular case of the life wheat cycle of most genotypes, Mg uptake is not significantly depressed by Ca and, therefore, an antagonistic interaction between these nutrients accumulations in the shoots is not expected to develop. Moreover, shoot Mg accumulation might display a synergistic pattern with chlorophylls accumulation during grain filling (Bergmann, 1992;Schoefs and Bertrand, 1997;Dias et al, 2009d), but at maturity, as the rate of Mg translocation from the roots tends to decrease (Dias et al, 2009d), the inhibition of chlorophylls accumulation might occur (Dias et al, 2009d).…”
Section: Mineral Nutritionmentioning
confidence: 99%
“…Nevertheless, it has been reported (Dias et al, 2009d) that, in the particular case of the life wheat cycle of most genotypes, Mg uptake is not significantly depressed by Ca and, therefore, an antagonistic interaction between these nutrients accumulations in the shoots is not expected to develop. Moreover, shoot Mg accumulation might display a synergistic pattern with chlorophylls accumulation during grain filling (Bergmann, 1992;Schoefs and Bertrand, 1997;Dias et al, 2009d), but at maturity, as the rate of Mg translocation from the roots tends to decrease (Dias et al, 2009d), the inhibition of chlorophylls accumulation might occur (Dias et al, 2009d). In durum wheat, further supporting a different extent of tolerance (Al-khatib and Paulsen, 1989;Maçãs et al, 1999Maçãs et al, , 2000Dias et al, 2009d;, at maturity Ca and Mg shoot accumulation in sensitive genotypes to heat stress might parallel with a diminishing chlorophyll content and a decreased net carbon assimilation rate (Dias et al, 2009d).…”
Section: Mineral Nutritionmentioning
confidence: 99%
See 1 more Smart Citation